Glycerol based binary solvent: Thermal properties study and its application in nanofluids. (March 2020) - Liu, Changhui; Qiao, Yu; Lv, Bingru; Zhang, Tianjian; Rao, Zhonghao
Abstract: Nanofluids are of great importance due to the superior performance on improvement of thermal performance. In this work, glycerol (GL) based binary solvent system, including GL/water (W), GL/ethylene glycol (EG), and GL/dimethyl sulfoxide (DMSO) were studied comprehensively regarding their melting points, boiling points, thermal conductivities and viscosities. Graphene oxide (GO), which was prepared through a chemical exfoliation method, was subsequently dispersed into those solvents to make nanofluids. Thermal conductivity and viscosities were studied to evaluate the performance of those nanofluids. It is revealed that a maximum 20% thermal conductivity enhancement of nanofluid is achieved by just filling 0.6  vol % of GO.